Prediction of silicon content in the hot metal using Bayesian networks and probabilistic reasoning - Wandercleiton Cardoso; Renzo di Felice (Universitas Ahmad Dahlan, 2021)
The blast furnace is the principal method of producing cast iron. In the production of cast iron, the control of silicon is vital because this impurity is harmful to almost all steels. Artificial neural networks with Bayesian regularization are more robust than traditional back-propagation networks and can reduce or eliminate the need for tedious cross-validation. Bayesian regularization is a mathematical process that converts a nonlinear regression into a